GROUNDWATER CONSERVATION MODEL ON RECHARGE AREA OF VOLCANIC SLOPE - Murtianto, Hendro; Woei Lin, Shyang; Chen, Zue-er (IJRDO-Journal of Applied Science, 2017)
Landuse change becomes common environmental issue in each country. In developing countries, landuse change from forest to agriculture and residential area, decrease the environment quality. The impacts of landuse change to aquifer are decreasing potential groundwater, trigger for land subsidence and changing soil ecosystem. The purpose of this study is developing model to conserve the degradation aquifer caused by landuse change. Recharge area has a big role to keep groundwater infiltrated to aquifer zone. Research location of this research is in Merapi Volcano, an active volcano in the world. Some methods applied to conserve the aquifer, such as: build infiltration wells, terraces, artificial lakes and replantation. The results of this research is a model conservation of groundwater that can improve water infiltration capacity and manage water storage in aquifer zone.